Principles and practice of surgery - Garden, O. James (Churchill Livingstone Elsevier, 2007)
Guides through various surgical topics that are encountered in an integrated medical curriculum and in subsequent clinical practice. This text enables the student to appreciate both the medical and surgical implications of diseases that are encountered in surgical wards